The Bikini Approach is Safe and Effective for Direct Anterior Approach THA - Weiner, Travis R.; Neuwirth, Alexander L.; Geller, Jeffrey A.; Shah, Roshan P.; Hickernell, Thomas R.; Cooper, H. John (The Journal of Hip Surgery, 2023)
Conventional incision orientation for direct anterior approach (DAA) total hip arthroplasty (THA) is longitudinal, paralleling fibers of the tensor fascia latae. Alternatively, a “bikini” incision can be oriented along Langer's lines. We sought to determine if there were any differences in surgical site complications (SSCs), mechanical complications, or reoperation between longitudinal and bikini DAA. We retrospectively reviewed 420 consecutive primary DAA THA by a single surgeon over a 2-year period. The surgeon was experienced with both incision orientations. Complications were recorded by chart review. Chi-square tests were used to examine for differences between categorical variables and t-tests for continuous variables. Longitudinal incisions were used in 320 patients (76.2%) while bikini incisions were used in 100 patients (23.8%). Women were significantly more likely to have a bikini incision (39.1% vs. 5.8%; p < 0.00001). Across the entire cohort, patients undergoing THA through either longitudinal or bikini incision had comparable rates of SSCs (4.7% vs. 5.0%; p = 0.90). With longitudinal incisions, SSCs were more likely to occur in obese patients compared with nonobese patients (8.3% vs. 3.1%; p = 0.04). With bikini incisions, there was no difference in the rate of SSCs between obese and nonobese patients (4.0% vs. 5.3%; p = 0.79). There were no differences in mechanical complications or rates of reoperation (0.3% vs. 0.0%; p = 0.58). Both longitudinal and bikini incisions are safe and effective ways to perform the DAA for primary THA, with no differences in rates of SSCs, mechanical complications, or reoperation. For obese patients in this series, the bikini incision was associated with a lower rate of SSCs but requires future study due to dissimilar study groups.
Keywords: total hip arthroplasty; direct anterior approach; bikini incision; longitudinal incision; wound complications; mechanical complications